TANGGUNG JAWAB KANTOR PENDAFTARAN FIDUSIA SEHUBUNGAN PENDAFTARAN FIDUSIA SECARA ELEKTRONIK YANG TIDAK MELAKUKAN PENGECEKAN DOKUMEN AKTA JAMINAN FIDUSIA DIHUBUNGKAN DENGAN UNDANG-UNDANG NOMOR 42 TAHUN 1999 TENTANG JAMINAN FIDUSIA - Sudriyo Sudriyo (President University, 2017)
Fiduciary registration is currently undergoing a shift in the digital era which provides a value and convenience for fiduciary owners, But the problem arises when the fiduciary registration does not provide the value of legal certainty and office accountability that dares to issue a fiduciary certificate without the process of checking data and fiduciary objects based on the above description the author takes the title: RESPONSIBILITY OF FIDUSIA REGISTRATION OFFICES IN CONNECTION OF ELECTRONIC FIDUSIA REGISTRATION THAT DOES NOT CONDUCT THE DOCUMENT OF FIDUSIA GUARANTEE CONNECTED TO LAW NUMBER 42 OF 1999 CONCERNING FIDUSIA GUARANTEE, Problem identification is electronic Fiduciary registration fulfilling legal certainty and in accordance with Law Number 42 of 1999 and What is the responsibility of Fiduciary registration office as the party issuing Fiduciary certificate in connection with electronic Fiduciary registration that does not carry out inspection towards the physical data of the Fiduciary Guarantee deed linked to Law Number 42 of 1999. The formation of this system is a manifestation of the Ministry of Justice and Human Right to uphold the contents of Article 14 Paragraph (1) of the Fiduciary Guarantee Law (FGL) which reads: